Generations of exclusion : Mexican Americans, assimilation, and race - Telles, Edward Eric, 1956- (Russell Sage Foundation, 2008)
"When boxes of original files from a 1965 survey of Mexican Americans were discovered in a dusty basement at UCLA, sociologists Edward Telles and Vilma Ortiz recognized a unique opportunity to examine how the Mexican American experience has evolved over the past four decades. Telles and Ortiz located and re-interviewed most of the original respondents and many of their children. Then, they combined the findings of both studies to construct a thirty-five year analysis of Mexican American integration into American society. Generations of Exclusion is the result of this extraordinary project. ... Generations of Exclusion measures Mexican American integration across a wide number of dimensions: education, English and Spanish language use, socioeconomic status, intermarriage, residential segregation, ethnic identity, and political participation. The study contains some encouraging findings, but many more that are troubling. ... Telles and Ortiz identify institutional barriers as a major source of Mexican American disadvantage. Chronic under-funding in school systems predominantly serving Mexican Americans severely restrains progress. Persistent discrimination, punitive immigration policies, and reliance on cheap Mexican labor in the southwestern states all make integration more difficult. The authors call for providing Mexican American children with the educational opportunities that European immigrants in previous generations enjoyed. The Mexican American trajectory is distinct - but so is the extent to which this group has been excluded from the American mainstream. .. Most immigration literature today focuses either on the immediate impact of immigration or what is happening to the children of newcomers to this country. Generations of Exclusion shows what has happened to Mexican Americans over four generations. In opening this window onto the past and linking it to recent outcomes, Telles and Ortiz provide a troubling glimpse of what other new immigrant groups may experience in the future."--Jacket